Neighbourhoods and oral health: Agent-based modelling of tooth decay. (September 2021) - Broomhead, T.; Ballas, D.; Baker, S.R.
Abstract: This research used proof of concept agent-based models to test various theoretical mechanisms by which neighbourhoods may influence tooth decay in adults. Theoretical pathways were constructed using existing literature and tested in two study areas in Sheffield, UK. The models found a pathway between shops and sugar consumption had the most influence on adult tooth decay scores, revealing that similar mechanisms influence this outcome in different populations. This highlighted the importance of the interactions between neighbourhood features and individual level variables in influencing outcomes in tooth decay. Further work is required to improve the accuracy and reliability of the models. Highlights: Relevant frameworks and theory can help to highlight the complexity of neighbourhood influences on oral health outcomes. Proof of concept ABMs found that a pathway with shops, diet and sugar consumption led to the greatest increases in decay. This pattern was seen in areas with both higher and lower socio-economic profiles. Pathways with dental related behaviours such as dental visits and toothbrushing did not significantly impact on decay scores.